Design, modeling, and optimization of nonlinear piezoelectric energy harvesters - Upadrashta, Deepesh (2017)
Over the past few years, structural health monitoring using wireless sensors has received significant emphasis to improve the safety, serviceability, and reliability of mechanical and civil structures. However, battery powered wireless sensors pose a critical issue of periodic replacement/recharge of the batteries which results in significant amount of maintenance cost. Moreover, the disposal of chemical batteries causes environmental hazard. With advancement in smart materials, low-power-consuming electronic devices, and integrated circuits, energy harvesting has emerged as a potential technology for powering wireless sensor nodes. Several ambient energy sources such as solar, wind, thermal gradient, and vibration are suitable for energy harvesting. However, the ubiquitous nature of vibration has encouraged researchers to opt it for energy harvesting through certain transduction mechanisms. Among various transduction mechanisms, energy harvesting from vibrations using piezoelectric materials has garnered a lot of academic focus because of its higher power density, high voltage output, and ease of application.